Australian survey of current practice and guideline use in adult cancer pain assessment and management: Perspectives of oncologists. Issue 2 (17th December 2012) - Luckett, Tim; Davidson, Patricia Mary; Boyle, Frances; Liauw, Winston; Agar, Meera; Green, Anna; Lovell, Melanie; ImPaCCT (Improving Palliative Care through Clinical Trials); PoCoG (Psycho‐oncology Co‐operative Research Group) Symptom Cluster Collaborative
Abstract Aims Cancer pain continues to be undertreated in up to half of cases, despite the availability of evidence‐based guidelines. This study aimed to: (i) identify barriers and facilitators to adult cancer pain assessment and management, as perceived by Australian health professionals; (ii) establish the perceived need for new Australian guidelines and implementation strategy; (iii) identify which guidelines are used; (iv) identify barriers and facilitators to guideline use. This article focuses on the perceptions of responding oncologists. Methods A cross‐sectional survey was administered online. Invitations were circulated via peak bodies and clinical leaders. Comments were coded independently by two researchers. Results In all 76 oncologists self‐reported high concordance with evidence‐based recommendations, except validated pain scales. Perceived barriers to pain management included insufficient non‐pharmacological interventions, access to /coordination between services, and time. Only 22 percent of respondents reported using pain guidelines. Perceived barriers to guideline use included lack of access, awareness and any single standard. Respondents were generally supportive of new Australian guidelines and especially an implementation strategy. Conclusion Barriers to evidence‐based practice and guideline use identified by our survey might be addressed via a clinical pathway that gives step‐by‐step guidance on evidence‐based practice along with a framework for evaluation. Particular attention should be paid to promoting use of validated scales, patient education and non‐pharmacological interventions, training of an appropriately skilled workforce and improving care coordination. Challenges are discussed.